2020
DOI: 10.1186/s10194-020-01113-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustained response to onabotulinumtoxin A in patients with chronic migraine: real-life data

Abstract: Background: Treatment with onabotulinumtoxin A (BT-A) is safe and effective for chronic migraine (CM). Several studies assessed possible predictors of response to treatment with BT-A, but there is little knowledge on the frequency and predictors of sustained response. The aim of this study was to evaluate sustained response to BT-A in patients with CM. Main body: In this prospective open-label study, 115 patients with CM and treated with BT-A were consecutively enrolled in two Italian headache centers and foll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
1
24
0
1
Order By: Relevance
“…In agreement with this survey, a real-world observational cohort study using the PREEMPT protocol suggests that approximately 25% of patients might not respond until after four treatment cycles and 1 year, cautioning against adjudicating responder/nonresponder status to avoid missing a significant percentage of patients who might benefit from onabotulinumtoxinA treatment [12]. Real-world data from headache centers in Italy also support the notion that the benefits of onabotulinumtoxinA treatment using the PREEMPT protocol are sustained, even in patients with a recent onset of CM [28]. Preliminary results also suggest that treatment using the PREEMPT protocol may be beneficial to patients with other chronic, difficult-to-treat headache disorders [29].…”
Section: Discussionmentioning
confidence: 94%
“…In agreement with this survey, a real-world observational cohort study using the PREEMPT protocol suggests that approximately 25% of patients might not respond until after four treatment cycles and 1 year, cautioning against adjudicating responder/nonresponder status to avoid missing a significant percentage of patients who might benefit from onabotulinumtoxinA treatment [12]. Real-world data from headache centers in Italy also support the notion that the benefits of onabotulinumtoxinA treatment using the PREEMPT protocol are sustained, even in patients with a recent onset of CM [28]. Preliminary results also suggest that treatment using the PREEMPT protocol may be beneficial to patients with other chronic, difficult-to-treat headache disorders [29].…”
Section: Discussionmentioning
confidence: 94%
“…Consistent with these guidelines, a quarter of Italian headache physicians surveyed believed that patients achieving a ≥ 30% reduction in headache days were considered responders (instead of ≥ 50% reduction), and 40% of these clinicians believed that more than 4 treatment cycles were required before classifying a patient as a nonresponder [ 20 ]. Also supporting this guidance, a real-world study demonstrated that patients who do not achieve a 50% reduction in headache days by the third onabotulinumtoxinA treatment cycle still exhibit improvements in disability and headache-related impact [ 21 ]. However, the outcomes measured may also impact the perception of treatment response, as a prospective study of patients with CM conducted in Spain showed that migraine-associated disability was more closely related to headache pain intensity than to headache frequency [ 22 ].…”
Section: Discussionmentioning
confidence: 98%
“…Evidence suggests that about one quarter of patients treated with BT-A who develop a response to the drug within the first two cycles might lose their response during the fourth cycle, while a comparable proportion of patients develop a new-onset response to BT-A during the third or fourth cycle [29]. Response to BT-A may fluctuate over time, and not all responders show a sustained response to the drug [29,30]. Fluctuations in response to BT-A might be common in the long term if we consider each single patient.…”
Section: Discussionmentioning
confidence: 99%